Recent advanced applications of metasurfaces in multi-dimensions - Yuan Quan; Ge Qin; Chen Linsen; Zhang Yi; Yang Yuhang; Cao Xun; Wang Shuming; Zhu Shining; Wang Zhenlin (Nanophotonics)
Unlike traditional optical components, which rely on the gradual accumulation of light along the optical path over a distance much larger than the wavelength to form a wavefront, metasurfaces manipulate light field properties on the wavelength thickness by specially arranging various meta-atoms. Due to the ease of integration and compact planar structure, metasurfaces play a key role in the light field manipulations. Here, we review the recent advances of metasurfaces in multi-dimensions, including light wavelength, polarization, orbital angular momentum(OAM), and angular response. Progress in these fields has brought new applications in areas such as imaging, display, communication, and information encryption, etc. Finally, we also discuss the challenges and prospects of metasurfaces applications.